2021
DOI: 10.1590/1983-40632021v5167857
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of phonolite as a potassium source for Paiaguás palisadegrass

Abstract: Potassium chloride (KCl) is the most widely used potassium source to meet crops requirements. However, Brazil’s dependence on imports to meet the national demand demonstrates the need to assess the efficiency of other sources of this nutrient. The present study aimed to assess the agronomic efficiency of phonolite in natura and its mixture with a water-soluble source (KCl), for Paiaguás palisadegrass. The experiment was conducted in a greenhouse, with a sandy clay loam typic Hapludox. A completely randomized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Tanzania and byCabral et al (2020), who fertilized several types of grass with ammonium sulfate, the same source used in this study, observed positive responses in the number of tillers in relation to fertilization performed with urea. Potassium also changes the leaves emission and tillers, asCruz et al (2021) observed an increase in leaves number of Urochloa brizantha cv. Paiaguás performing fertilization with increasing levels of potassium andCabral et al (2017) verified an increase in tillers number of Mulato II cultivar, a hybrid of Urochloa spp.…”
mentioning
confidence: 86%
“…Tanzania and byCabral et al (2020), who fertilized several types of grass with ammonium sulfate, the same source used in this study, observed positive responses in the number of tillers in relation to fertilization performed with urea. Potassium also changes the leaves emission and tillers, asCruz et al (2021) observed an increase in leaves number of Urochloa brizantha cv. Paiaguás performing fertilization with increasing levels of potassium andCabral et al (2017) verified an increase in tillers number of Mulato II cultivar, a hybrid of Urochloa spp.…”
mentioning
confidence: 86%